The dinoflagellate cysts Thalassiphora subreticulata n.sp. and Thalassiphora balcanica: their taxonomy, ontogenetic variation and evolution. (2nd April 2020) - Mudie, Peta J.; Fensome, Robert A.; Rochon, André; Bakrač, Koraljka
Abstract: Thalassiphora and other large 'winged' dinoflagellate cysts common in Oligocene–Pliocene stratified epicontinental seas display morphological variation greater than the plasticity of extant taxa, thereby raising questions about causes. This variation has been attributed either to directed ontogeny in response to salinity or oxygen gradients or to evolutionary development in response to special environmental conditions. Some authors have grouped certain taxa that mark the closing phases of European Paratethyan basins into an intergradational plexus including species of Thalassiphora, Galeacysta, Nematosphaeropsis and cruciform Spiniferites . Spiniferites (previously Thalassiphora ) balcanicus and Galeacysta etrusca were considered end members of this plexus, despite large differences in morphology. We re-evaluate interpretations of the plexus through comparison primarily with a new north-western Atlantic Eocene species Thalassiphora subreticulata and new Croatian material of Thalassiphora balcanica, and we comment on differences from other Thalassiphora species. The large Eocene species Thalassiphora subreticulata (up to 148 µm maximum dimension) is camocavate, and has a coarsely reticulo-fibrous, irregularly perforate periphragm forming a shallow, bowl-shaped structure, as in Thalassiphora pelagica. Electron microscopy shows the perforations are crossed by fibrils in accord with a proposed 'stretched net' model of periphragm development. The smaller Late Miocene Paratethyan species Thalassiphora balcanica (maximum dimension to 115 µm) is also camocavate, with a similar fibrous periphragm which encloses about half the ventral surface and has smooth-edged and open perforations. Scanning electron microscope images show this species lacks the branched spinous processes used to justify its transfer from Thalassiphora to Spiniferites by Sütő-Szentai. In both Thalassiphora species, morphological variations do not support either the benthic–planktonic stage ontogenetic model or the oxidation-state model previously proposed for Thalassiphora pelagica. Among 30 species currently assigned to Thalassiphora, no correlation was found between cyst size and age. However, the range of morphology in this genus points to the need for taxonomic re-assessment, which might help reveal evolutionary trends.